How to Measure the Entrepreneurial Competences of SME’s Using the Rasch Model? - Edi Fitriana Afriza; Rendra Gumilar; Betanika Nila Nirbita (Dinamika Pendidikan, 2023)
This study focused on measuring the entrepreneurial competence of MSME actors in the post-pandemic period. A purposive sampling technique was utilized to recruit the respondents. The respondents encompassed perpetrators, owners, and managers of SMEs assisted by the Indonesian Business Development Services Association (ADBSI) given government assistance (N=100). Technically, the Rasch Model was employed to measure Entrepreneurial competency since it is assumed to be the most appropriate model for quantitative data analysis in the field of human sciences. It enables the researchers to produce ordinal data. Tests with Winstep were carried out on entrepreneurial competency data in the pandemic era. They covered: summary statistics, item measures and Wright maps, item (column) fit order, item test (dimensionality), rating (partial–credit) scale test, differential item functional (DIF) test and probability value. The results of the study proved that the applied entrepreneurial competency instrument indicated good persons, Cronbach Alpha, and item reliability. The personal reliability coefficient obtained a value of 0.88. An item of 0.76 revealed good and fairly good. The results of one of the instruments were considered the most essential aspects related to entrepreneurial competencies. The competencies should be possessed by students to face the post-pandemic business competition.